2015
DOI: 10.2460/javma.247.8.945
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suicide, attitudes toward mental illness, and practice-related stressors among US veterinarians

Abstract: In this survey, approximately 1 in 11 veterinarians had serious psychological distress and 1 in 6 experienced suicidal ideation since leaving veterinary school. Implementing measures to help veterinarians cope with practice-related stressors and reducing barriers veterinarians face in seeking mental health treatment might reduce the risk for suicide among veterinarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
190
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(239 citation statements)
references
References 29 publications
17
190
3
3
Order By: Relevance
“…1 Indeed, the risk of death by suicide among veterinarians across various countries reportedly ranges from 1.7 to 4 times the risk of the general population. 24 Additionally, the reported prevalence of major depression in veterinarians ranges from 20% to 66%, 57 and a recent study 6 revealed that 9% of a large sample (n = 11,627) of US veterinarians have experienced serious psychological distress, 6 compared with 3.2% of the general US population. 8 In light of the high risks of suicide, depressive symptoms, and psychological distress, the veterinary profession has been identified by both academic and popular media entities as needing more research to identify factors contributing to this profession-wide problem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Indeed, the risk of death by suicide among veterinarians across various countries reportedly ranges from 1.7 to 4 times the risk of the general population. 24 Additionally, the reported prevalence of major depression in veterinarians ranges from 20% to 66%, 57 and a recent study 6 revealed that 9% of a large sample (n = 11,627) of US veterinarians have experienced serious psychological distress, 6 compared with 3.2% of the general US population. 8 In light of the high risks of suicide, depressive symptoms, and psychological distress, the veterinary profession has been identified by both academic and popular media entities as needing more research to identify factors contributing to this profession-wide problem.…”
mentioning
confidence: 99%
“…14,15 Considering this relationship between practice-related stressors and depression as well as the disproportionate risks of depressive symptoms, serious psychological distress, and suicide among veterinarians versus the general population, it is important to understand the full range of practice-related stressors experienced by veterinarians that might be contributing to mental health problems across the profession. 6 …”
mentioning
confidence: 99%
“…298 Workplaces should also strive to create a safe, supportive environment in which mental health issues are not stigmatized. Shelter veterinarians are at high risk for developing depression, 299 and many spay-neuter veterinarians possess demographic risk factors that may place them at greater risk than other veterinarians for experiencing depression, burnout, compassion fatigue, or suicidal ideation. 299,300 Access to mental health care may be increased by posting information about mental health services, support groups, and suicide hotline numbers in staff areas and by providing flexibility in staff scheduling or duties to accommodate mental health treatment.…”
Section: Leadershipmentioning
confidence: 99%
“…Shelter veterinarians are at high risk for developing depression, 299 and many spay-neuter veterinarians possess demographic risk factors that may place them at greater risk than other veterinarians for experiencing depression, burnout, compassion fatigue, or suicidal ideation. 299,300 Access to mental health care may be increased by posting information about mental health services, support groups, and suicide hotline numbers in staff areas and by providing flexibility in staff scheduling or duties to accommodate mental health treatment. Workers may be trained to recognize early signs of stress, compassion fatigue, and depression in themselves and others, and programs should provide a supportive atmosphere and referral to mental health services.…”
Section: Leadershipmentioning
confidence: 99%
“…Also of importance is the emerging literature relating to an increased risk of suicide within animal-related professions, in particular the veterinary profession (Bartram and Baldwin 2010, Skipper and Williams 2012, Nett et al 2015. While this area of study is very relevant in the context of this chapter, the mechanisms underlying a person's propensity to commit suicide are a complete area of study within itself.…”
Section: Discussionmentioning
confidence: 99%